2020
DOI: 10.1096/fj.201903226rr
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic‐sensing of the skeletal muscle clock coordinates fuel oxidation

Abstract: Abbreviations: Bmal1, brain and muscle Arnt-like protein 1; CLOCK, circadian locomotor output cycles kaput; MyHC, myosin heavy chain; ROR, RAR-related orphan receptor. AbstractCircadian clock confers temporal control in metabolism, with its disruption leading to the development of insulin resistance. Metabolic substrate utilization in skeletal muscle is coordinated with diurnal nutrient cycles. However, whether the molecular clock is involved in this coordination is largely unknown. Using a myocyte-selective g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 51 publications
0
15
0
Order By: Relevance
“…Hyperinsulinemic-euglycemic clamp studies were performed at the Mouse Metabolism and Phenotyping Core at Baylor College of Medicine as described previously ( 63 , 64 ). Mice were anesthetized, and a midline neck incision was made to expose the jugular vein.…”
Section: Methodsmentioning
confidence: 99%
“…Hyperinsulinemic-euglycemic clamp studies were performed at the Mouse Metabolism and Phenotyping Core at Baylor College of Medicine as described previously ( 63 , 64 ). Mice were anesthetized, and a midline neck incision was made to expose the jugular vein.…”
Section: Methodsmentioning
confidence: 99%
“…Harfmann et al demonstrated that post developmental loss of Bmal1, a regulator of circadian rhythm, in skeletal muscle leads to decreased fat mass, impaired glucose uptake, and insulin resistance [111]. Similar results are seen by others where a loss of muscle Bmal1 leads to the upregulation of lipid metabolism and down-regulation of glucose oxidation [112][113][114]. Additionally, loss of other clock components leads to decreased skeletal muscle mass and function [115].…”
Section: Fastingmentioning
confidence: 65%
“…Therefore, shortened photoperiods may promote a switch toward an OSA phenotype, and potentially explain why OSA symptoms are more severe in the winter (Cassol et al, 2012). One explanation for the decrease in RER under L5 may be that altering photoperiod drives changes in peripheral expression patterns of clock genes, which can have direct effects on glucose and lipid metabolism (Sosniyenko et al, 2010; Sen et al, 2018; Yin et al, 2020). However, further studies are needed to understand the contributions of photoperiodic changes in clock gene expression to metabolic and ventilatory patterns.…”
Section: Discussionmentioning
confidence: 99%